Political Transformation of Electoral Lawmaking: Towards Fair and Transparent Elections - Suriyanti, Lili; Suganda, Atma; Ismail, Ismail (Pelopor Publikasi Akademika, 2024)
General elections are the main pillar of democracy that aims to guarantee the political rights of every citizen in a fair manner. However, election regulations in Indonesia still face obstacles, such as inequality in the allocation of legislative seats, the dominance of political elite interests, the lack of representation of marginalised groups, and the lack of transparency in the legislative process. This research uses a normative juridical method to analyse the gap between the principles of substantive justice mandated by the constitution and the reality of the implementation of election regulations, as well as to offer a political reconstruction of law based on substantive justice. The novelty of the research lies in the proposed incentive mechanism in the form of additional funding for political parties that succeed in increasing women's representation in parliament as well as the application of a technology-based open legislative system to increase transparency and public participation. Reconstruction based on three main pillars - equality, representation, and transparency - is expected to improve the legitimacy of elections, create inclusive democracy, and strengthen the values of Pancasila and the 1945 Constitution.